A toxicological survey of acute psychoses in Cape Coloured males with special reference to the cannabinoids - Rottanburg, Dawn (Department of Psychiatry and Mental Health, 2018)
Many South African psychiatrists, and particularly those working in psychiatric hospitals with Black and Coloured patients, have the firm clinical impression that in many of these patients acute psychotic illness is associated with the abuse of cannabis. Most of the previous work in this field had been done by clinicians of Eastern countries where the use of cannabis has been endemic for thousands of years. However, those workers were handicapped because they lacked both the sophisticated techniques for standardized psychiatric evaluation and the availability of an assay to confirm cannabis use. It was decided to investigate acute psychoses in Cape Coloured males admitted to Valkenberg Hospital with the following aims: i. To identify a cohort of acutely psychotic patients who had recently been using cannabis and to compare them with a matched control group who were free of any drugs. The recently available EMITR immunochemical analytical technique was used for the detection of urinary cannabinoids. To exclude the contribution of other psychotropic agents to the aetiology of the psychoses, gas chromatography was performed to detect ethanol and thin-layer chromatography to screen for other psychotropic agents. ii. To assess the comprehensive mental state of patients on admission and then again after a 7-10 day period the Present State Examination (PSE), a well validated and standardized diagnostic instrument, was used. iii. To determine serum creatinine phosphokinase (CPK) and serum lactate dehydrogenase (LDH) levels (indicators of muscle damage) in view of the published reports of elevated levels in psychotic patients.